2015
DOI: 10.1158/1940-6207.capr-14-0110
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention Activity of 25-Hydroxyvitamin D in the MMTV-PyMT Mouse Model of Breast Cancer

Abstract: Development of oncologic conditions is often accompanied by inadequate vitamin D status. The chemoprevention ability of this molecule is of high interest for breast cancer, the most common malignancy in women worldwide. Because current effective vitamin D analogues, including the naturally occurring active metabolite 1,25-dihydroxycholecalciferol (1,25(OH) 2 D), frequently cause hypercalcemia at pharmacologic doses, the development of safer molecules for clinical chemopreventive use is essential. This study ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 66 publications
0
42
0
1
Order By: Relevance
“…Even in animal studies, however, the specific vitamin D metabolites that act on pre-neoplastic or transformed cells to mediate anti-tumor effects have not been precisely defined. One study indicated that chronic systemic administration of 25D via implanted mini-pumps lead to accumulation of both 25D and 1,25D in transgenic mouse mammary tumors, supporting the concept that tumors accumulate 25D and synthesize 1,25D (41). However, no studies have systematically measured accumulation of vitamin D or 25D in breast tissue or tumors as a function of dietary vitamin D or in relation to storage in normal body pools.…”
Section: Vitamin D Storage and Uptake In Mammary Gland And Breast Canmentioning
confidence: 95%
See 1 more Smart Citation
“…Even in animal studies, however, the specific vitamin D metabolites that act on pre-neoplastic or transformed cells to mediate anti-tumor effects have not been precisely defined. One study indicated that chronic systemic administration of 25D via implanted mini-pumps lead to accumulation of both 25D and 1,25D in transgenic mouse mammary tumors, supporting the concept that tumors accumulate 25D and synthesize 1,25D (41). However, no studies have systematically measured accumulation of vitamin D or 25D in breast tissue or tumors as a function of dietary vitamin D or in relation to storage in normal body pools.…”
Section: Vitamin D Storage and Uptake In Mammary Gland And Breast Canmentioning
confidence: 95%
“…In one study, administration of 25D to polyoma middle T antigen-mouse mammary tumor virus breast cancer model (PyMT-MMTV) elevated tumor 1,25D levels, delayed tumor development and decreased lung metastasis (41). In a second study using the same model, Li et al (59) reported that deletion of Cyp27b1 from the mammary epithelium accelerated tumorigenesis, up-regulated cell proliferation, angiogenesis, cell cycle progression and survival markers in tumors and elevated several known oncogenic pathways (AKT, NF-κB and STAT3).…”
Section: Role Of Cyp27b1 In Mammary Gland and Breast Cancermentioning
confidence: 99%
“…We and others have shown that supplementation with dietary vitamin D or treatment with its active hormonal form calcitriol [1,25(OH) 2 D 3 ] exhibits multiple actions to inhibit BCa growth as demonstrated in cultured BCa cells and in lean mouse models of BCa (Deeb, et al 2007; Feldman, et al 2014; Rossdeutscher, et al 2015; Shui and Giovannucci 2014; So and Suh 2015; Welsh 2012). These vitamin D actions include the transcriptional repression of aromatase ( Cyp19 ) (Krishnan, et al 2010; Swami, et al 2011), inhibition of Er expression (Swami, et al 2000; Swami, et al 2013), and suppression of cyclooxygenase-2 (COX-2) expression (Moreno, et al 2005) leading to the reduction in the synthesis of pro-inflammatory mediators such as PGE 2 that are major stimulators of aromatase transcription in BCa (Brown and Simpson 2010; Simpson and Brown 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Since breast cancer metastasis greatly reduces the survivability of the cancer, the impact of these studies, when translated to the clinic and general population, may have a significant impact to reduce mortality associated with breast cancer. (Ren et al, 2012;Hauser, Walsh, Shrotriya, & Karafa, 2014;Neuhouser et al, 2008;Mohr, Gorham, Kim, Hofflich, & Garland, 2014 (Rossdeutscher et al, 2014). In addition to studies in vivo, studies in cell models also support the hypothesis that 1,25(OH) 2 D or its analogues inhibit metastasis, including invasion through matrigel and migration of MCF-7 and MCF10DCIS cells, and changes in expression of markers of metastatic capability.…”
Section: Impact Of 125(oh) 2 D On Mmp Mrna Expressionmentioning
confidence: 83%